Micro-Osteoperforations Accelerate Tooth Movement without Exacerbating the Progression of Root Resorption in Rats - Tadasu Sugimori; Masaru Yamaguchi; Jun Kikuta; Mami Shimizu; Shinichi Negishi (Biomolecules, 2024)
A recent study reported that micro-osteoperforations (MOPs) accelerated tooth movement by activating alveolar bone remodeling. However, very little is known about the relationship between MOPs and external apical root resorption during orthodontic treatment. In this study, in order to investigate the mechanism through which MOPs accelerate tooth movement without exacerbating the progression of root resorption, we measured the volume of the resorbed root, and performed the terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-biotin nick-end labeling (TUNEL) method on exposed MOPs during experimental tooth movements in rats. Male Wistar rats (11 weeks old) were divided into three groups: 10 g orthodontic force (optimal force) applied to the maxillary first molar (optimal force: OF group), 50 g orthodontic force application (heavy force: HF group), and 10 g force application plus three small perforations of the cortical plate (OF + MOPs group). On days 1, 4, 7, 10, and 14 after force application, the tooth movement and root volume were investigated by micro-computed tomography. Furthermore, the number of apoptotic cells in the pressured sides of the periodontal ligament (PDL) and surrounding hard tissues were determined by TUNEL staining. The OF + MOPs group exhibited a 1.8-fold increase in tooth movement on days 7, 10, and 14 compared with the OF group. On days 14, the HF group had a higher volume of root loss than the OF and OF + MOPs groups. On the same day, the number of TUNEL-positive cells in the HF group increased at the root (cementum) site whereas that in the OF group increased at the alveolar bone site. Furthermore, the number of TUNEL-positive cells in the OF + MOPs group increased at the alveolar bone site compared with the OF group. These results suggest that MOPs accelerate orthodontic tooth movement without exacerbating the progression of root resorption.